Cigarette smoke extract reduces the anti-inflammatory effect of fluticasone in human airway smooth muscle cells - Alghamdi, Abdulrhman (2019)
Background: Airway inflammation is a hallmark of asthma disease, and cytokines play a major role in the inflammation process. Human airway smooth muscle cells (HASMCs) are considered as an important source of inflammatory cytokines and chemokines in Asthma. Inhaled corticosteroids (ICS) are used with asthmatic patients as anti-inflammatory therapy to control the severity of the disease and maintain lung function. Clinical studies suggest asthmatic smokers do not respond to steroid as well as non-smokers, but whether cigarette smoke can reduce steroid sensitive in vitro is unclear. We hypothesise that cigarette smoke extract (CSE) reduces the anti-inflammatory effect of fluticasone in HASMCs.